Determining a Digital Marketing Strategy Using a Combination of Analytical Network Process (ANP) and Profile Matching - Dakwah, Muhammad Mujahid; Roodhi, Mohammad Najib; Suprayetno, Djoko; Kusmayadi, Iwan; Abdurrahman, Abdurrahman; Hammad, Rifqi (Universitas Bumigora, 2024)
Background: Many MSMEs in the city of Matram are experiencing diculties in determining the digital marketing strategy to use. This is due to the many digital marketing strategies that can be used and the many factors that serve as criteria for selection.Objective: Develop a decision support system using a combination of ANP and profile-matching methods to assist MSMEs in determining the digital marketing strategy to be used.Methods: The method used in this research is a combination of ANP and Profile Matching Methods.Result: The combination of methods (ANP) and Profile Matching in determining digital marketing strategies has an accuracy of 83.33%.Conclusion: The combination of ANP and Profile Matching methods in determining digital marketing strategies has successfully recommended the best digital marketing strategy.